1929 Neb. Laws 673–74, ch. 190, §§ 1–2 - (:unkn) unknown (General Publisher, 1929)
Prohibited selling or otherwise disposing of a machine gun. Punishable by fine of $1,000-$10,000. Also Prohibited transporting or possessing a machine gun. Punishable by imprisonment for 1-10 years.
--
Keywords: MACHINE GUN RESTRICTION